Flame-retardant smoke-suppression EPS (Expandable Polystyrene) composite material and preparation method thereof
By using flame retardants and hydrogel powder containing tea polyphenols, sucrose, phytic acid and other ingredients on EPS boards to form a multi-layer defense line, the problems of flammability and toxic smoke of EPS foam are solved, and efficient flame retardant and smoke suppression effects and improved thermal stability of the material are achieved.
Patent Information
- Application Number
- CN202510798740.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-16
- Publication Date
- 2025-09-23
AI Technical Summary
Existing EPS foam materials are flammable and produce large amounts of black smoke and toxic gases when burned. Traditional flame retardants such as bromides are harmful to the environment. It is necessary to develop green halogen-free flame retardants to improve their flame retardant and smoke suppression properties.
Tea polyphenols, sucrose, phytic acid and other ingredients are used as flame retardants, combined with hydrogel powder, and a multi-layer defense line is formed on the EPS board through sol-gel technology. Tea polyphenols generate a carbon layer at high temperature to prevent heat transfer, sucrose carbonizes to absorb heat, hydrogel powder absorbs moisture and flame retardant, and phosphorus forms phosphate compounds to enhance the density of the carbon layer.
It significantly improves the flame retardant properties and smoke suppression effect of EPS materials, reduces smoke release, enhances the thermal stability of the material and the density of the carbon layer, and reduces the generation of harmful gases.
Smart Images

Figure CN120682526A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lightweight, fireproof and heat-insulating materials used in the construction and packaging industries, and particularly relates to a flame-retardant and smoke-suppressing EPS composite material and a preparation method thereof. Background Art
[0002] Expandable polystyrene (EPS) foam offers excellent thermal insulation, outstanding water resistance, aging resistance, good toughness, and easy processing and molding, making it widely used in building exterior wall insulation. However, EPS foam is inherently flammable, producing large amounts of black smoke and molten droplets during combustion. Furthermore, the increasing demand for EPS foam to reduce energy consumption has made it imperative to improve its flame retardancy and smoke suppression properties.
[0003] By coating the surface of EPS foam balls, its fire resistance can be greatly improved. In the existing pretreatment, most flame retardant foamable EPS processes simply coat the reagent directly on each spherical particle, and the flame retardant process is relatively simple.
[0004] Currently, brominated flame retardants are widely used. Although they have high flame retardant efficiency, they produce a large amount of toxic gases during combustion, which can cause irreversible effects on the human body, such as immunotoxicity, endocrine disorders, reproductive toxicity, and cancer. Therefore, research on green halogen-free flame retardants for EPS is a very promising approach. Summary of the Invention
[0005] In order to solve the above problems, the present invention provides a flame retardant and smoke suppressing EPS composite material and a preparation method thereof.
[0006] The present invention is achieved by the following technical solution: a flame-retardant and smoke-suppressing EPS composite material, wherein EPS foam pellets coated with a flame retardant agent are solidified to form an EPS board coated with a flame retardant solution, and then hydrogel powder is sprayed onto the EPS board coated with the flame retardant solution using sol-gel technology; the mass ratio of the flame retardant agent to the EPS pellets is 0.3-0.7:1, and the mass ratio of the hydrogel powder to the EPS board is 0.1-0.2:3; Wherein: the flame retardant agent is a mixture of a charring flame retardant tea polyphenol, a smoke suppressant sucrose, an organophosphorus flame retardant phytic acid and water in a mass ratio of 3:2:1:30; The hydrogel powder is prepared by mixing acrylic acid, sodium hydroxide, N,N'-methylenebisacrylamide, potassium persulfate and water in a mass ratio of 2500:1120:5:8:8000.
[0007] The method for preparing the flame-retardant and smoke-suppressing EPS composite material comprises the following steps: (1) Pre-foaming the expandable polystyrene to obtain pre-foamed particles; the specific pre-foaming method is: heating the EPS microbeads at 98°C for 15-20 minutes for pre-foaming, and then cooling at room temperature for 24 hours to obtain pre-foamed particles with a diameter of 3-5 mm; (2) Mixing the pre-foamed particles and the flame retardant solution in proportion and stirring thoroughly to obtain foam balls coated with the flame retardant solution; (3) drying the foam balls obtained above and placing them into a mold, heating them again to expand and solidify them, and then cooling and ejecting them to obtain an EPS board coated with a flame retardant solution; (4) Preparation of hydrogel powder: At room temperature, a solution of acrylic acid and sodium hydroxide with a neutralization degree of 80% was prepared, wherein the concentration of acrylic acid was 35% and the mass was 5g, and the concentration of sodium hydroxide solution was 25% and the mass was 2.24g. Then, 0.01g of N,N'-methylenebisacrylamide was added as a cross-linking agent and 0.016g of potassium persulfate was added as an initiator. The solution was grafted at 70℃ for 90min to form a hydrogel. The formed hydrogel was then washed, soaked, dried and crushed. The crushed hydrogel was then dried at 60℃ for 12h to obtain hydrogel powder. (5) The above-obtained board is sprayed with hydrogel powder to obtain the flame-retardant and smoke-suppressing EPS insulation board.
[0008] The flame retardant solution is prepared by first mixing tea polyphenols and sucrose, and then adding phytic acid and water in proportion.
[0009] The heating temperature for thermal expansion curing molding in step (3) is 110-120°C and the time is 20-30 minutes.
[0010] The invention covers the prepared hydrogel powder on the formed EPS insulation board, so that the hydrogel powder covered on the polystyrene board becomes the first line of defense, and the flame retardant on the original sphere serves as the second line of defense.
[0011] The present invention adds tea polyphenols to the flame retardant solution, wherein the content of catechin accounts for the highest proportion in the tea polyphenols. The monomer epigallocatechin gallate (EGCG) in catechin contains a high content of benzene rings and phenolic hydroxyl groups, which has the advantage of being an expandable carbon source. At the same time, the condensed ring structure formed by decomposition and recombination will combine with the styrene monomer and be fixed to the carbon layer. When heated, gas will be generated inside, which promotes the expansion of the carbon layer and prevents further transfer of oxygen and heat.
[0012] By adding sucrose to the flame-retardant solution, the new material expands and carbonizes when heated, preventing further oxygen and heat transfer. At high temperatures, it decomposes first, absorbing the radiated heat and carbonizing, preventing further decomposition of the matrix. Furthermore, due to its viscosity, sucrose absorbs soot particles released into the air during combustion.
[0013] By spraying hydrogel powder on the foam board, the powder has the ability to absorb moisture in the air and has super strong water retention capacity, which has a flame retardant effect. At the same time, it releases H· during combustion, and further dehydration condensation promotes the carbonization of the flame retardant agent, which can significantly improve the synergistic flame retardant and smoke suppression effect of the board.
[0014] When exposed to high temperatures, the synthetic flame retardant solution decomposes before the matrix, absorbing excess heat and generating phosphorus oxide radicals (PO·, PO2·). These free radicals capture reactive free radicals (HO·, H·), interrupting the combustion chain reaction. Phosphorus also cross-links within the carbon layer to form phosphate structures, further enhancing its density. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 These are digital photographs of the carbon residue after burning of Comparative Example 1 and Examples 1, 2, and 3 of the present invention; in the figures: (a) is a digital photograph of the carbon residue after burning of Comparative Example 1; (b) is a digital photograph of the carbon residue after burning of Example 1; (c) is a digital photograph of the carbon residue after burning of Example 2; and (d) is a digital photograph of the carbon residue after burning of Example 3. Figure 2 The SEM micrographs of Examples 1, 2, and 3 of the present invention are shown in the figures: (a) is a SEM micrograph of Example 1; (b) is a SEM micrograph of Example 2; and (c) is a SEM micrograph of Example 3. Figure 3 The EDS element mapping diagram of the carbon residue after burning in Example 2 of the present invention is shown in the figure: (a) is a SEM panoramic image, (b) is an EDS mapping diagram of the C element, (c) is an EDS mapping diagram of the O element, and (d) is an EDS mapping diagram of the P element; Figure 4 This is an XPS spectrum of the carbon residue after burning in Example 2 of the present invention; Figure 5 The Raman spectra of the carbon residue after burning of Example 1 and Example 2 of the present invention are shown in FIG. 1 : (a) is the Raman spectra of the carbon residue after burning of Example 1 and Example 2; Figure 6 3D images of TG-IR at different temperatures for Comparative Example 1 and Example 2 of the present invention; (a) is a 3D image of TG-IR at different temperatures for Comparative Example 1; (b) is a 3D image of TG-IR at different temperatures for Example 2; Figure 7 TG-IR plane diagrams of Comparative Example 1 and Example 2 of the present invention at different temperatures; in the figure: (a) is the TG-IR plane diagram of Comparative Example 1 at different temperatures; (b) is the TG-IR plane diagram of Example 2 at different temperatures. DETAILED DESCRIPTION
[0016] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all the embodiments; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0017] Unless defined otherwise, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention belongs, and the disclosure and materials cited therein are hereby incorporated by reference.
[0018] Technical equivalents to the specific embodiments described that are apparent to those skilled in the art using no more than routine experimentation are intended to be encompassed by this application.
[0019] The experimental methods in the following examples, unless otherwise specified, are all conventional methods. The instruments and equipment used in the following examples, unless otherwise specified, are all conventional laboratory instruments and equipment; the experimental materials used in the following examples, unless otherwise specified, are all purchased from conventional biochemical reagent stores.
[0020] Comparative Example 1: Preparation of pre-foamed EPS board: (1) Expandable polystyrene is pre-foamed to obtain pre-foamed particles.
[0021] (2) The obtained foam balls are dried and placed in a mold, heated at 110-120°C for 20-30 minutes to expand and solidify the mold, and then cooled and ejected to obtain the EPS board.
[0022] Comparative Example 2: Preparation of flame-retardant EPS board with tea polyphenols as flame retardant: (1) Expandable polystyrene is pre-foamed to obtain pre-foamed particles.
[0023] (2) At room temperature, stir 0.75g of tea polyphenols and 7.5g of water to make a flame retardant solution.
[0024] (3) The pre-foamed EPS particles and the flame retardant solution are fully stirred, wherein the EPS particles are 3 g, to obtain foam balls coated with the flame retardant solution. The foam balls are then dried and placed in a mold, heated at 110-120°C for 20-30 minutes to expand and solidify the mold, and cooled and ejected to obtain an EPS board coated with the flame retardant solution.
[0025] Comparative Example 3: Preparation of polystyrene insulation board, the flame retardant solution is prepared from 0.75g tea polyphenols, 0.25g phytic acid and 7.5g water, and the other methods are the same as those described in Comparative Example 2.
[0026] Comparative Example 4: Polystyrene insulation board, the flame retardant solution is prepared from 0.75g tea polyphenols, 0.3g ferric sulfate, 0.25g phytic acid and 7.5g water, and the other methods are the same as those described in Comparative Example 2.
[0027] Comparative Example 5: Polystyrene insulation board, the flame retardant solution is prepared from 0.75g tea polyphenols, 0.6g magnesium sulfate, 0.25g phytic acid and 7.5g water, and the other methods are the same as those described in Comparative Example 2.
[0028] Comparative Example 6: Polystyrene insulation board, the flame retardant solution is prepared from 0.75g tea polyphenols, 0.6g copper acetate, 0.25g phytic acid and 7.5g water, and the other methods are the same as those described in Comparative Example 2.
[0029] Comparative Example 7: Polystyrene insulation board, the flame retardant solution is prepared from 0.75g tea polyphenols, 0.6g zinc borate, 0.25g phytic acid and 7.5g water, and the other methods are the same as those described in Comparative Example 2.
[0030] Comparative Example 8: Polystyrene insulation board, the flame retardant solution is prepared from 0.75g tea polyphenols, 0.3g calcium carbonate, 0.25g phytic acid and 7.5g water, and the other methods are the same as those described in Comparative Example 2.
[0031] Example 1: A flame-retardant and smoke-suppressing EPS insulation board, wherein the flame-retardant solution is prepared from 0.75 g of tea polyphenols, 0.5 g of sucrose, 0.25 g of phytic acid and 7.5 g of water. Other methods are the same as those described in Comparative Example 2.
[0032] Example 2: Preparation of flame-retardant and smoke-suppressing EPS composite material: (1) Expandable polystyrene is pre-foamed to obtain pre-foamed particles.
[0033] (2) At room temperature, 0.75g of tea polyphenols, 0.5g of sucrose, 0.25g of phytic acid and 7.5g of water were stirred evenly to prepare a flame retardant solution.
[0034] (3) The pre-foamed EPS particles and the flame retardant solution are fully stirred, wherein the EPS particles are 3 g, to obtain foam balls coated with the flame retardant solution. The foam balls are then dried and placed in a mold, heated at 110-120°C for 20-30 minutes to expand and solidify the mold, and cooled and ejected to obtain an EPS board coated with the flame retardant solution.
[0035] (4) At room temperature, a solution of acrylic acid and sodium hydroxide with a neutralization degree of 80% was prepared, wherein the acrylic acid concentration was 35% (5 g) and the sodium hydroxide solution was 25% (2.24 g). 0.01 g of N,N'-methylenebisacrylamide was added as a crosslinker, and 0.016 g of potassium persulfate was added as an initiator. The solution was then placed in a drying oven at 70°C for grafting for 90 minutes. The resulting hydrogel was then washed, soaked, dried, and crushed. The crushed hydrogel was then placed in a drying oven at 60°C for 12 hours to obtain the desired hydrogel powder.
[0036] (5) Spray 0.2 g of hydrogel powder around the center of the plate obtained above to obtain the flame retardant and smoke-suppressing EPS composite material.
[0037] Example 3: Preparation of flame-retardant and smoke-suppressing EPS composite material, the specific method is as follows: (1) Expandable polystyrene is pre-foamed to obtain pre-foamed particles.
[0038] (2) At room temperature, 0.75g of tea polyphenols, 0.5g of sucrose, 0.25g of phytic acid and 5.25g of water were stirred evenly to prepare a flame retardant solution.
[0039] (3) The pre-foamed EPS particles and the flame retardant solution are fully stirred, wherein the EPS particles are 3 g, to obtain foam balls coated with the flame retardant solution. The foam balls are then dried and placed in a mold, heated at 110-120°C for 20-30 minutes to expand and solidify the mold, and cooled and ejected to obtain an EPS board coated with the flame retardant solution.
[0040] (4) At room temperature, a solution of acrylic acid and sodium hydroxide with a neutralization degree of 80% was prepared, wherein the acrylic acid concentration was 35% (5 g) and the sodium hydroxide solution was 25% (2.24 g). 0.01 g of N,N'-methylenebisacrylamide was added as a crosslinker, and 0.016 g of potassium persulfate was added as an initiator. The solution was then placed in a drying oven at 70°C for grafting for 90 minutes. The resulting hydrogel was then washed, soaked, dried, and crushed. The crushed hydrogel was then placed in a drying oven at 60°C for 12 hours to obtain the desired hydrogel powder.
[0041] (5) Spray 0.2 g of hydrogel powder around the center of the plate obtained above to obtain the flame retardant and smoke-suppressing EPS composite material.
[0042] The products obtained in Examples 1-3 and Comparative Examples 1-8 were subjected to performance tests, including compressive strength, thermal conductivity, limiting oxygen index, vertical burning grade, and total smoke production. The compressive strength test was conducted in accordance with GB / T8813-2008 Rigid Foam Plastics - Determination of Compression Properties and GB / T32981-2016 Determination of Equivalent Thermal Conductivity of Wall Materials; the limiting oxygen index test was conducted in accordance with GB / T2406.2-2009 Plastics - Determination of Combustion Behavior by Oxygen Index Method; the vertical burning grade test was conducted in accordance with GB / T2408-2008 Plastics - Test for Combustion Performance - Horizontal and Vertical Methods; and the total smoke production test was conducted in accordance with ASTM E 1354 / ISO 5660-1. The performance results are shown in Table 1.
[0043] Table 1: Test results As shown in Table 1, the thermal insulation board prepared in Example 2 has the best comprehensive performance. Compared with the pure board in Comparative Example 1, the compressive strength is increased by 107%, the limiting oxygen index is increased by 220%, and the total smoke emission is reduced by 71.9%.
[0044] Comparative Examples 2 and 3, compared to Example 1, were obtained by reducing some of the reagents in Example 2. It was found that the effect achieved when only some of the reagents were used was far inferior to that of Example 2. Example 3 increased the concentration of the flame retardant solution compared to Example 2, achieving better flame retardancy, but at the same time, performance in terms of smoke emission suppression declined. Comparative Examples 4 to 8 were compared with currently commonly used smoke suppressants, demonstrating that Example 1 of the present invention achieved even better results.
[0045] In order to explore the flame retardant and smoke suppression mechanism of the flame retardant in Example 2, SEM, XPS and Raman were used to detect the carbon residue after the cone calorimetry experiment. The experiment found that Figure 1 The control sample had almost no carbon residue after burning, and even the bottom tin foil could be seen. However, the amount of carbon residue increased significantly after adding the flame retardant. As the concentration of the flame retardant increased, the amount of carbon residue also increased accordingly, playing an important role in isolating heat and oxygen. SEM showed that Figure 2 The EPS carbon residue in Example 1 has many holes and a loose structure, which affects the flame retardant performance. After adding the hydrogel powder, the holes on the surface of the carbon layer are significantly reduced, the carbon layer is more dense, and the heat insulation and oxygen isolation effects are significantly improved. In order to further analyze the composition of the carbon residue, EDS and XPS analysis were performed on the carbon residue after the cone calorimetry test. The EDS analysis revealed that the constituent elements in the carbon layer are uniformly dispersed. A large amount of P element was also found in the carbon residue, proving the presence of phosphorus-containing compounds in the condensed phase, such as Figure 3 .
[0046] In addition, XPS further analyzes the elemental composition and chemical bond analysis of the carbon residue, such as Figure 4 In the P2p spectrum, a PO bond was found at 133.5ev and a P=O bond was found at 134.4ev. At the same time, signal peaks at 531.7ev and 533.4ev were observed in O1s, which were attributed to COP and P=O bonds respectively, which also corresponded to the P signal peak of the P2p spectrum. This is the result of the production of organic phosphoric acid, indicating that when the flame retardant is pyrolyzed, P will be decomposed and intertwined with the residual carbon and remain in the carbon layer, which can prove that P is flame retardant in the form of a condensed phase.
[0047] Raman spectroscopy is often used to characterize microstructures and is an important experiment for characterizing the degree of graphitization. -1 There are two characteristic peaks in the Raman spectrum, corresponding to the D band and G band of carbon. D / I G The value indicates that the degree of graphitization is high and the carbon layer is denser. The integral area ratio of the residual carbon peak in Example 1 is as low as 0.54, which is further reduced by 31.5% after adding the hydrogel powder, indicating that the decomposition of the hydrogel effectively promotes the formation of the graphitized carbon layer during the combustion process. Figure 5 .
[0048] Through comprehensive characterization of SEM, EDS, XPS and Raman spectroscopy, the results show that the EPS composite material after adding flame retardant has high thermal stability, dense carbon residue characteristics and a high degree of graphitization. At the same time, the P element in the flame retardant is evenly dispersed and interwoven in the carbon layer.
[0049] The pyrolysis products in the gas phase during combustion are of great significance to the intensity of the fire and the analysis of the mechanism of smoke generation and release. Therefore, the use of TG-IR further determines the law of the change of pyrolysis products in the gas phase with temperature. According to the TG-IR plane diagram at 420℃, it can be found that Figure 7 The absorption peak of Example 2 is less than that of the sample in Comparative Example 1, which means that the types of combustible gases produced are relatively small and the release of gaseous products is suppressed.
[0050] By analyzing the pyrolysis gas phase absorption peak of the control sample, it can be known that Figure 7At 420 °C, a variety of pyrolysis products are released, among which 3074, 1495 and 695 correspond to the benzene ring of EPS. This temperature corresponds to the maximum mass loss rate in TG, indicating that combustion is occurring and a large amount of smoke is released. At the same time, absorption peaks can be observed at 1942, 1630, and 910, which are mainly attributed to the CH stretching vibration, C=C stretching vibration and CH2 bending vibration of styrene. However, these substances are rarely observed in the subsequent heating process, indicating that styrene has been completely released or completely depolymerized at 420 °C, while 2363 and 1941 indicate the release of CO2 and CO, and there are also peaks in the subsequent heating process. On the contrary, the absorption peaks of Example 2 are relatively simple compared with the sample of Comparative Example 1. There is only a relatively obvious CO2 absorption peak at 2361 and a few absorption peaks representing EPS benzene rings at 3074, but the peaks are weaker than those of Comparative Example 1. At the same time, no phosphorus characteristic peaks are detected in the gas phase product, indicating that the phosphorus element is effectively captured by the solid carbon layer, and the carbon chains are connected by POC bonds to form a dense cross-linked structure, indicating that the release of gas phase products is better suppressed.
[0051] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the above embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A flame-retardant and smoke-suppressing EPS composite material, characterized by: The EPS foam balls coated with flame retardant agent are solidified to form EPS sheets coated with flame retardant solution. Then, hydrogel powder is sprayed on the EPS sheets coated with flame retardant solution using sol-gel technology. The mass ratio of flame retardant agent to EPS balls is 0.3-0.7:1, and the mass ratio of hydrogel powder to EPS sheets is 0.1-0.2:
3. Wherein: the flame retardant agent is a mixture of a charring flame retardant tea polyphenol, a smoke suppressant sucrose, an organophosphorus flame retardant phytic acid and water in a mass ratio of 3:2:1:30; The hydrogel powder is prepared by mixing acrylic acid, sodium hydroxide, N,N'-methylenebisacrylamide, potassium persulfate and water in a mass ratio of 2500:1120:5:8:8000.
2. A method for preparing the flame-retardant and smoke-suppressing EPS composite material according to claim 1, characterized in that: The steps include: (1) Pre-foaming the expandable polystyrene to obtain pre-foamed particles; the specific pre-foaming method is: heating the EPS microbeads at 98°C for 15-20 minutes for pre-foaming, and then cooling at room temperature for 24 hours to obtain pre-foamed particles with a diameter of 3-5 mm; (2) Mixing the pre-foamed particles and the flame retardant solution in proportion and stirring thoroughly to obtain foam balls coated with the flame retardant solution; (3) drying the foam balls obtained above and placing them into a mold, heating them again to expand and solidify them, and then cooling and ejecting them to obtain an EPS board coated with a flame retardant solution; (4) Preparation of hydrogel powder: At room temperature, a solution of acrylic acid and sodium hydroxide with a neutralization degree of 80% was prepared, wherein the concentration of acrylic acid was 35% and the mass was 5g, and the concentration of sodium hydroxide solution was 25% and the mass was 2.24g. Then, 0.01g of N,N'-methylenebisacrylamide was added as a cross-linking agent and 0.016g of potassium persulfate was added as an initiator. The solution was grafted at 70℃ for 90min to form a hydrogel. The formed hydrogel was then washed, soaked, dried and crushed. The crushed hydrogel was then dried at 60℃ for 12h to obtain hydrogel powder. (5) The above-obtained board is sprayed with hydrogel powder to obtain the flame-retardant and smoke-suppressing EPS insulation board.
3. The preparation method according to claim 2, wherein: The flame retardant solution is prepared by first mixing tea polyphenols and sucrose, and then adding phytic acid and water in proportion.
4. The preparation method according to claim 2, wherein: The heating temperature for thermal expansion curing molding in step (3) is 110-120°C and the time is 20-30 minutes.